Chaos and periodicity in Vallis model for El Niño - Borghezan M.* (2017)
© 2017 Elsevier LtdWe investigate a two-dimensional parameter-space of a three-parameter, three-variable, continuous-time dynamical system, namely the Vallis model for El Niño phenomenon. We report on modifications in this parameter-space, as a function of the third parameter which is varied. More specifically we report on organization of chaos and periodicity, showing the existence of periodic structures embedded in a chaotic region, which are organized in period-adding sequences.